ORIGIN OF CONSTRUCTION TERMS (International conference on multidisciplinary science, 2023)
The article deals with the linguistic research of Uzbek construction terms and the history of the emergence of an explanatory dictionary of Uzbek architectural-construction terms and the theoretical issues of its creation. Methodological conclusions are given about the tasks, problems and their solutions, the relevance of creating a dictionary of construction-architecture terms. Focusing on the description of the works carried out in Uzbek and Russian linguistics in this field, the scope of these works is evaluated